Assessment of avoidable yield losses due to insect pests and diseases in wheat (Triticum aestivum) - JADHAV, MAHESH M; S, CHANDER; SAHARAN, M S; SUROSHE, SACHIN S; RAJNA, S (The Indian Journal of Agricultural Sciences, 2023)
Biotic stress, including insect pests and diseases, poses a significant constraint to the cultivation of food grain crops including wheat (Triticum aestivum L.) which is affected by several pests. Therefore, the present study was carried out during winter (rabi) seasons of 2020–21 and 2021–22 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to assess the yield loss due to multiple pests in a holistic manner with wheat variety HD 3086 (Pusa Gautami). Estimated avoidable yield loss due to higher aphid infestation and minimum disease incidences of Karnal bunt and black point disease during both the seasons (2020–21 and 2021–22) was 7.79% and 6.10%, respectively. Meanwhile, in treatment with a lower aphid infestation and minimum disease incidence of Karnal bunt and black point diseases, yield losses were 4.80% and 6.90% in 2020–21 and 2021–22, respectively. Incidences of the diseases were found to be minimal in both the seasons, thus the estimated avoidable losses attributed to aphids to a large extent.